Carriage of antibiotic-resistant Enterobacteriaceae in hospitalised children in tertiary hospitals in Harare, Zimbabwe. Issue 1 (December 2017) - Magwenzi, Marcelyn; Gudza-Mugabe, Muchaneta; Mujuru, Hilda; Dangarembizi-Bwakura, Mutsa; Robertson, Valerie; Aiken, Alexander
Abstract Background Extended-spectrum β-lactamase-producing and gentamicin resistantEnterobacteriaceae are increasingly recognised as a major cause of infection in low-income countries. We assessed the prevalence of gastrointestinal carriage of these bacteria in hospitalised children in Harare, Zimbabwe. Methods We conducted a cohort study in paediatric inpatients at two tertiary-referral hospitals between May and July 2015. Rectal swabs and faecal samples were collected within 24 h of admission and further follow-up samples were collected on alternate days during hospitalization. Disc-based, selective and enrichment methods were used to detect carriage of these two forms of resistance. Standard methods were used to confirm resistance status and determine the susceptibility of resistant isolates to other commonly-used antibiotics. Results One hundred and sixty four paediatric inpatient admissions (median age = 1.0 year, IQR = 0.2–2.2years) were enrolled, and an average of 1.9 faecal samples per patient were collected. On admission, 68/164 (41%) patients had both ESBL and gentamicin-resistantEnterobacteriaceae detected, 18 (11%) had ESBL only, 17 (10%) had gentamicin resistance only and 61 (37%) had negative screening for both forms of resistance. During hospitalisation, 32/164 (20%) patients were found to have a type of resistant organism which was not present in their admission sample. We found that faecal samples and use of a selective enrichment broth enhanced the detection of resistant organisms. Amongst resistant bacteria isolated, there were high levels of resistance to ciprofloxacin and chloramphenicol, but not ertapenem. Conclusions More than half of children had enteric carriage of a clinically-relevant form of antibiotic resistance on admission to public-sector hospitals in urban Zimbabwe. Additionally, a fifth of children acquired a further form of resistance during hospitalisation. Urgent action is needed to tackle the spread of antibiotic resistant enteric bacteria in African hospitals.